Factors responsible for the protection of Iraq’s sovereignity under international law - Qader, Mohammed Mustafa; Masum, Ahmad; Abdul Rahman, Rohana; Mikail, Ibrahim Kawuley; Abdullah, Mohamad Ainuddin Iskandar Lee (Medwell Journal, 2016)
The US coalition with alliance forces that invaded into Iraq since 2003 has really traumatise the state of Iraq’s political economy, security and peaceful co-existence of the citizens in Iraq and beyond. This sinister has degraded the image of Iraq before the committee of nations and relegated its sovereignty to the background which metamorphosed some experts to describe Iraq as a failed state. This study aims to ascertain the factors that guarantee the protection of Iraq’s sovereignty within the context of international law. The qualitative technique via interview and observation was duly adopted as the methods for data collection, whereby manual analysis was employed to present the result obtained from the field. The authors engaged experts among judges, members of the academia and diplomats into in-depth interview for this purpose. The study revealed that internal and external factors are held responsible as far as the protection of Iraq’s sovereignty under international law is concerned. The Iraqi citizens are yearning for their country to be governed based on its own traditions and legal norms. It is also viewed that the total disengagement of Iraq from foreign dominance (US Coalition) would lead Iraq to attain its sovereignty. The study concluded that, all room that would guarantee sovereignty of Iraq was blocked and intimidated by foreign powers. Hence, total disengaging Iraq from foreign dominance (US Coalition) and allowing the Iraqi’s to govern their own country is among the recommendations put forward in this study.